160 Echocardiographic assessment of CRT candidates. Does additional scar evaluation by MRI improve prediction of response?. (17th January 2020) - Duchenne, J; Cvijic, M; Larsen, C K; Galli, E; Aalen, J M; Voros, G; Beela, A S; Unlu, S; Penicka, M; Hopp, E; Bogaert, J; Smiseth, O A; et al.
Abstract: Background: Myocardial scar presence and extent, has a considerable influence on response to cardiac resynchronization therapy (CRT). Apical rocking (ApRock) and septal flash (SF) are associated with favourable outcome after CRT. Little is known however to which extent visual assessment of mechanical dyssynchrony by ApRock, SF and scar predicts CRT response. We therefore investigated, if additional scar assessment by cardiac magnetic resonance imaging (MRI) adds to the predictive value of the visual evaluation of echocardiographic images in CRT candidates. Methods: A total of 201 unselected patients referred for CRT, who fulfil the contemporary guidelines for CRT implantation, were enrolled in this prospective multicentre study. Two experienced observers visually assessed echocardiographic images before CRT implantation, focussing on the presence of ApRock, SF and location and extent of scar segments of the left ventricle (LV), resulting in a CRT response prediction (i.e. Integrative Prediction). A third observer provided a consensus reading in case of disagreement. All observers were blinded to all patient information other than the ischaemic aetiology of heart failure. Independent from that, segmental myocardial scar burden was objectified by late gadolinium enhancement (LGE) cardiac MRI (LGE > 50%). CRT response was defined as ≥15% reduction in LV end-systolic volume on echocardiography, one year after device implantation. Results: Overall, 69 (34%) patients had an ischaemic aetiology of heart failure. Before CRT, ApRock and SF were present in 129 (64%) and 136 (68%) patients, respectively. ApRock and SF alone predicted CRT response with an area under the curve (AUC) of 0.85 (95% CI: 0.79-0.91) and 0.84 (95% CI: 0.77-0.91) (Figure A), while the echocardiographic Integrative Prediction had an AUC of 0.90 (95% CI: 0.84-0.95), with a sensitivity of 93% and a specificity of 87% for the prediction of CRT response (Figure B) (p < 0.05 vs. ApRock and SF alone). When combining information on ApRock, SF and the number of scarred segments on MRI in a statistical model, the AUC was comparable to the echocardiographic Integrative Prediction [0.90 (95% CI: 0.84-0.96)] as was sensitivity and specificity (91% and 83%, respectively, p = N.S. vs. Integrative Prediction) (Figure C). Conclusions: An integrative visual assessment of LV function has an excellent predictive value for CRT response. Our data show, that the echocardiographic estimation of scar burden is sufficiently accurate and cannot be further improved by an additional MRI scar assessment.